Biographie d’un esprit au corps brisé. Les pierres magiques des ancêtres zapara d’Amazonie : des sujets du passé - Anne-Gaël Bilhaut (Journal de la Société des Américanistes, 2006)
Life of a spirit in a broken body. The magic stones of Zapara’s ancestors in Lowland Amazonia : subjects of the past. The use of magic stones in the Amazon has been studied by many ethnographers. However, the analysis of the intersubjective relations that occur between these stones and their « master » remains succinct. The example of the stones of the Zapara offers an understanding of these relations. The ancestors of the Ecuadorian Zapara (Amazonia) left on the land many stones that, when found by humans, become subjects to be treated as such. Stones of the ancestors with whom they share a history, are passed on from generation to generation, directly or indirectly. This article tells the story of a spirit embodied in a stone whose story has been reconstructed by the Zapara through its description and narrations. Possessed by an ancestor then passed on to his descendants, this « stone subject » then lost its mineral body, which then modified the relation between the stone and its master.